Multiple solutions to a nonlinear elliptic equation involving Paneitz type operators - Abdallah El Hamidi (International Journal of Mathematics and Mathematical Sciences)
This paper deals with an elliptic equation involving Paneitz type operators on compact Riemannian manifolds with concave-convex nonlinearities and a real parameter. Nonlocal and multiple existence results are established. Characteristic values of the real parameter are introduced and their role in the change of the energy sign and the existence of positive solutions are highlighted.